2022
DOI: 10.1177/08862605221106189
|View full text |Cite
|
Sign up to set email alerts
|

Who is the Practitioner in Faculty-Staff Sexual Misconduct Work?: Views from the UK and US

Abstract: This article maps and compares four universities’ policies and procedures for addressing faculty and staff sexual misconduct in higher education in the UK and US. While universities have engaged in significant work to grapple with student-student sexual misconduct, attention to misconduct perpetrated, and experienced, by higher education employees is relatively nascent. In this paper, we explore the maze of institutional processes and actors that victim-survivors of FASSM might encounter. We describe what is k… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 34 publications
(65 reference statements)
0
1
0
Order By: Relevance
“…Despite the government's usability of laws and regulations, studies by Page (2022), Coy et al (2022), and Soeung (2021) have shown that teachers' indiscipline behaviours are widespread worldwide. The study conducted by Young and Wiley (2021) in South America highlighted the occurrence of teachers engaging in sexual harassment towards students.…”
Section: Issn 2278 -0211 (Online)mentioning
confidence: 99%
“…Despite the government's usability of laws and regulations, studies by Page (2022), Coy et al (2022), and Soeung (2021) have shown that teachers' indiscipline behaviours are widespread worldwide. The study conducted by Young and Wiley (2021) in South America highlighted the occurrence of teachers engaging in sexual harassment towards students.…”
Section: Issn 2278 -0211 (Online)mentioning
confidence: 99%